2021
DOI: 10.1101/2021.01.12.426365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The lethal triad: SARS-CoV-2 Spike, ACE2 and TMPRSS2. Mutations in host and pathogen may affect the course of pandemic

Abstract: Variants of SARS-CoV-2 have been identified rapidly after the beginning of pandemic. One of them, involving the spike protein and called D614G, represents a substantial percentage of currently isolated strains. While research on this variant was ongoing worldwide, on December 20th 2020 the European Centre for Disease Prevention and Control reported a Threat Assessment Brief describing the emergence of a new variant of SARS-CoV-2, named B.1.1.7, harboring multiple mutations mostly affecting the Spike protein. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“… 58 Using a similar approach, Yurkovetskiy et al 59 showed how D614G changes affect the conformation of the S1 domain in the SARS-CoV-2 spike; the association rate between D614G and ACE2 being slower than that between D614 and ACE2 and the dissociation rate of D614G being faster and resulting in a lower affinity. In silico studies by Calcagnile et al 60 predicted that D614G replacement could drastically change the peptide secondary structure by replacing the (intracellular) C-terminal β-sheet with the α-helix in the region close to the mutation with a consequent increase in flexibility and variations in affinity between ACE2 and the D614G spike. However, unlike the T478K mutation, the D614G mutation is peculiar to both variants studied here.…”
Section: Resultsmentioning
confidence: 99%
“… 58 Using a similar approach, Yurkovetskiy et al 59 showed how D614G changes affect the conformation of the S1 domain in the SARS-CoV-2 spike; the association rate between D614G and ACE2 being slower than that between D614 and ACE2 and the dissociation rate of D614G being faster and resulting in a lower affinity. In silico studies by Calcagnile et al 60 predicted that D614G replacement could drastically change the peptide secondary structure by replacing the (intracellular) C-terminal β-sheet with the α-helix in the region close to the mutation with a consequent increase in flexibility and variations in affinity between ACE2 and the D614G spike. However, unlike the T478K mutation, the D614G mutation is peculiar to both variants studied here.…”
Section: Resultsmentioning
confidence: 99%